2016
DOI: 10.1007/s00125-016-4039-8
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin reduces obesity-associated insulin resistance in mice by activating AMPKα1 signalling in adipose tissue macrophages

Abstract: Aims/hypothesis Inflammatory polarisation of adipose tissue macrophages (ATMs) plays a critical role in the development of obesity-associated metabolic diseases such as insulin resistance and diabetes. Our previous study indicated that dietary luteolin (LU) could prevent the establishment of insulin resistance in mice fed a high-fat diet (HFD). Here, we further investigated the effects of LU, which is a natural flavonoid, on pre-established insulin resistance and obesityassociated ATM polarisation in mice. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 41 publications
0
63
0
Order By: Relevance
“…AMPK directly activates ULK1 through the phosphorylation of Ser 317 and Ser 777 to facilitate autophagy (22). In addition, luteolin regulates AMPK signaling in numerous other circumstances, including enhancing the survival of human umbilical vein endothelial cells against oxidative stress by modulating AMPK/protein kinase c pathway (52), improving atherosclerosis in mice via regulating AMPK/sirtuin1 signaling in macrophages (53) and reducing obesity-associated insulin resistance in mice by activating AMPK signaling in adipose tissue macrophages (54). In the present study, notably, the protective effect of luteolin was also abolished by the AMPK inhibitor compound c, as demonstrated by the decreased Lc3 II and Beclin1 expression, enhanced p62 expression, destabilized mitochondrial membrane potential, and increased cardiomyocyte apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…AMPK directly activates ULK1 through the phosphorylation of Ser 317 and Ser 777 to facilitate autophagy (22). In addition, luteolin regulates AMPK signaling in numerous other circumstances, including enhancing the survival of human umbilical vein endothelial cells against oxidative stress by modulating AMPK/protein kinase c pathway (52), improving atherosclerosis in mice via regulating AMPK/sirtuin1 signaling in macrophages (53) and reducing obesity-associated insulin resistance in mice by activating AMPK signaling in adipose tissue macrophages (54). In the present study, notably, the protective effect of luteolin was also abolished by the AMPK inhibitor compound c, as demonstrated by the decreased Lc3 II and Beclin1 expression, enhanced p62 expression, destabilized mitochondrial membrane potential, and increased cardiomyocyte apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, AMPK ameliorates insulin resistance in obesity [10,11,25,26]. It has been reported that AMPK activators specifically suppressed the expression of pro-inflammatory genes and the activation of NF-κB-mediated signaling [27,28]. The molecular mechanism for NF-κB activation is: (1) the degradation of IκB in a ubiquitin-dependent manner is triggered through its phosphorylation by IKK; (2) IκB degradation results in nuclear translocation of NF-κB [29].…”
Section: Discussionmentioning
confidence: 99%
“…T. cordifolia contains diverse type of chemical compounds, such as flavonoids, alkaloids, and some tannins (Singh & Chaudhuri, ). Quercetin (Arias, Macarulla, Aguirre, Martinez‐Castano, & Portillo, ), kaempferol (Alkhalidy et al, ), luteolin (Zhang et al, ), and epicatechin (Cremonini, Bettaieb, Haj, Fraga, & Oteiza, ) showed their antidiabetic effects via enhancing insulin secretion and insulin sensitization. The synergistic action of those components could regulate blood glucose in diabetic animals.…”
Section: Discussionmentioning
confidence: 99%